Numerical modeling investigation of long-term hydrologic change due to surface water and groundwater withdrawals from a high Andean headwater basin, southern Peru - Stansfield, William J., author; Ronayne, Michael J., advisor; Cooper, David, committee member; Sanford, William, committee member (Colorado State University. Libraries, 2024)
Reliable surface water and groundwater resources are of critical importance in the arid central Andes of Southern Peru. Low elevation cities and towns in coastal regions are dependent on water derived from relatively humid mountains and high elevation basins on the Andean Altiplano. The Huaytire Basin, located on the Altiplano at approximately 4,450 meters above mean sea level, is a headwater basin that has experienced hydrologic change in recent years. Surface water diversions from the perennial Lake Suches began in the 1960s, followed by groundwater pumping starting in the 1980s. These water development activities have been accompanied by observations of declining surface water quantity in the downgradient Rio Callazas and deteriorating phreatophytic vegetation within the basin itself. A review of precipitation and pan evaporation data from weather stations in the region did not reveal any clear climate-related trends that would impact water resource availability. A numerical groundwater flow model was constructed using MODFLOW to estimate the impact of long-term pumping on local hydrology and to investigate the sustainability of the Huaytire Basin pumping regime. The model accounted for groundwater-surface water interaction, including lake-aquifer exchange and stream-aquifer exchange along three major streams that originate within the basin. Surface water levels and flow rates were computed as part of the numerical solution, dependent on the simulated hydraulic head in the aquifer, which controls the amount of groundwater-surface water exchange. Three different recharge scenarios were considered to acknowledge uncertainty associated with groundwater recharge rates on the Altiplano. All three scenarios resulted in the study area converting from an open basin with surface water outflow to a closed basin within 50 years of the start of development. Other simulated impacts of pumping include a reduction in the stage and areal extent of Lake Suches and significant reductions in head-dependent outflows for the aquifer system. Relative to predevelopment conditions, groundwater discharge to Lake Suches, groundwater discharge to gaining stream reaches, phreatophytic evapotranspiration, and underflow out of the basin were all lower at the end of the 63-year transient simulation (by ~ 9.5, 50, 18, and 51%, respectively, using base-case recharge rates). It was concluded that groundwater development in the Huaytire Basin is a key factor that explains the observed hydrologic changes and that current pumping rates may be unsustainable.
Keywords: geoscience; hydrogeology; geology; hydrology; groundwater